Association of ionizing radiation dose from common medical diagnostic procedures and lymphoma risk in the Epilymph case-control study - Pasqual, Elisa; Turner, Michelle C; Gracia-Lavedan, Esther; Casabonne, Delphine; Benavente, Yolanda; Chef, Isabelle Thierry; Maynadié, Marc; Cocco, Pierluigi; Staines, Anthony; Foretova, Lenka; Nieters, Alexandra; Boffetta, Paolo; et al. (PloS one, 2020)
Medical diagnostic X-rays are an important source of ionizing radiation (IR) exposure in the general population; however, it is unclear if the resulting low patient doses increase lymphoma risk. We examined the association between lifetime medical diagnostic X-ray dose and lymphoma risk, taking into account potential confounding factors, including medical history. The international Epilymph study (conducted in the Czech-Republic, France, Germany, Ireland, Italy, and Spain) collected self-reported information on common diagnostic X-ray procedures from 2,362 lymphoma cases and 2,465 frequency-matched (age, sex, country) controls. Individual lifetime cumulative bone marrow (BM) dose was estimated using time period-based dose estimates for different procedures and body parts. The association between categories of BM dose and lymphoma risk was examined using unconditional logistic regression models adjusting for matching factors, socioeconomic variables, and the presence of underlying medical conditions (atopic, autoimmune, infectious diseases, osteoarthritis, having had a sick childhood, and family history of lymphoma) as potential confounders of the association. Cumulative BM dose was low (median 2.25 mGy) and was not positively associated with lymphoma risk. Odds ratios (ORs) were consistently less than 1.0 in all dose categories compared to the reference category (less than 1 mGy). Results were similar after adjustment for potential confounding factors, when using different exposure scenarios, and in analyses by lymphoma subtype and by type of control (hospital-, population-based). Overall no increased risk of lymphoma was observed. The reduced ORs may be related to unmeasured confounding or other sources of systematic bias.We found little evidence that chronic medical conditions confound lymphoma risk and medical radiation associations.
Keywords: lymfom; logistické modely; Bone Marrow; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; ionizující záření; Radiation, Ionizing; Female; rizikové faktory; Aged; dospělí; senioři; lidé; Lymphoma; Adult; ženské pohlaví; Male; Middle Aged; dávka záření; kostní dřeň; radiační expozice; Odds Ratio; Radiation Exposure; Radiation Dosage; mužské pohlaví; odds ratio; Logistic Models; Risk Factors